The Practicality and Effectiveness of Direct Learning Model by Using Life-Based Learning Approach - Annita Kastur; Mustaji Mustaji; Yatim Riyanto (Studies in Learning and Teaching, 2020)
This study aims to produce a direct learning model with a life-based learning approach that is feasible, practical, and effective to improve the learning outcomes of students at Morris Sidoarjo. This research method uses the Dick and Carey development model with the one-group pretest-posttest design research design. The data collection process was carried out using observation, questionnaires, and giving tests to students. The research instruments obtained were student activity questionnaires, student response questionnaires, learning observation sheets, and student learning outcomes tests. The sample of this research is 20 students at the Morris Sidoarjo course. The research indicated that the direct learning model with a life-based learning approach was practical in its use to improve course participants' learning outcomes at Morris Sidoarjo in the Yogyakarta, which was shown by the excellent category of learning and activity of students. Second, the direct learning model with a life-based learning approach is effective in improving the learning outcomes of course participants at Morris Sidoarjo in the Yogyakarta, which is shown by the results of the calculation of the N-Gain test showing an increase in learning outcomes with a value of 0.8 in the high category. From these results, the model built with a life-based learning approach can be implied as an alternative and reference for developing learning models in course institutions.